Spirometry-adjusted fraction of exhaled nitric oxide increases accuracy for assessment of asthma control in children - Martins, C (2017)
Spirometry and exhaled nitric oxide are two important complimentary tools to identify and assess asthma control in children. We aimed to determine the ability of a new suggested spirometry-adjusted fraction of exhaled nitric oxide (NO) index in doing that. A random sample of 1602 schoolchildren were screened by a health questionnaire, skin prick tests, spirometry with bronchodilation and exhaled NO. A total of 662 children were included with median (IQR) exhaled NO 11(14) ppb. Receiver operating characteristic (ROC) curves using exhaled NO equations from Malmberg, Kovesi and Buchvald, and spirometry-adjusted fraction of exhaled NO values were applied to identify asthmatic children and uncontrolled asthma. Receiver operating characteristic (ROC) curves failed to identify asthmatic children (all AUC<0.700). Spirometry-adjusted fraction of exhaled NO/FEV1 (AUC=0.712; P=.010) and NO/FEF25%-75% (AUC=0.735 P=.004) had a fair and increased ability to identify uncontrolled disease compared with exhaled NO (AUC=0.707; P=.011) or the Malmberg equation (AUC=0.701; P=.014). Sensitivity and specificity identifying non-controlled asthma were 59% and 81%, respectively, for the cut-off value of 9.7ppb/L for exhaled NO/FEV1, and 40% and 100% for 15.7ppb/L/s for exhaled NO/FEF25%-75%. Exhaled NO did not allow to identify childhood asthma. Spirometry-adjusted fraction of exhaled NO performed better-assessing asthma control in children. Thus, although more validation studies are needed, we suggest its use in epidemiological studies to assess asthma control.